The effects of boron‐supplemented diets on adipogenesis‐related gene expressions, anti‐inflammatory, and antioxidative response in high‐fat fed rats. Issue 2 (23rd November 2022) - Kucukkurt, Ismail; Ince, Sinan; Eryavuz, Abdullah; Demirel, Hasan H.; Arslan‐Acaroz, Damla; Zemheri‐Navruz, Fahriye; Durmus, Ibrahim
Abstract: The fatty liver syndrome caused by nutritional factors is a common cause of hepatic dysfunction globally. This research was designed to study the shielding effect of boron in rats fed a diet having high fat. Overall, 40 Wistar albino male rats were placed into one control and four treatment groups, that is,  each having eight rats. Group I was provided with a standard rat diet while group II was only provided a high‐fat diet for 60 days. Groups III, IV, and V were provided with 5, 10, and 20 mg/kg/day boron, respectively, by gastric gavage besides a high‐fat diet for 60 days. Malondialdehyde was increased significantly in rats' blood and tissue because of high‐fat diets. Glutathione was decreased significantly in blood and tissues because of a high‐fat diet. Moreover, the activities of superoxide dismutase (SOD) and catalase (CAT) were decreased in the blood and tissues of the high‐fat‐fed rats. The genes expression for C‐reactive protein, interleukin‐1β, leptin, and tumor necrosis factor‐α were increased while gene expression for peroxisome proliferator‐activated receptors was decreased in the liver of rats fed with a high‐fat diet. Contrariwise, boron supplementation improves antioxidative response in terms of increased SOD and CAT activities, gene expression regulation, and improved anti‐inflammatory activities. In a nutshell, boron has dose‐dependent shielding antioxidative and tissue regenerative effects in rats.